2002
DOI: 10.1128/aac.46.9.2765-2771.2002
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Increases Susceptibility of Mycobacterium tuberculosis to Isoniazid

Abstract: Isoniazid is a first-line antibiotic used in the treatment of infections caused by Mycobacterium tuberculosis.Isoniazid is a prodrug requiring oxidative activation by the catalase-peroxidase hemoprotein, KatG. Resistance to isoniazid can be obtained by point mutations in the katG gene, with one of the most common being a threonine-for-serine substitution at position 315 (S315T). The S315T mutation is found in more than 50% of isoniazid-resistant clinical isolates and results in an Ϸ200-fold increase in the MIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 48 publications
3
41
0
3
Order By: Relevance
“…Quinones generate reactive oxygen species that can damage lipids, proteins and deoxyribonucleic acids. Published works have postulated that the activity of β-lapachone and other quinones against bacteria and Trypanosoma cruzi is due to superoxide and hydrogen peroxide formation (Cruz et al 1978, Bulatovic et al 2002, Salas et al 2008.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quinones generate reactive oxygen species that can damage lipids, proteins and deoxyribonucleic acids. Published works have postulated that the activity of β-lapachone and other quinones against bacteria and Trypanosoma cruzi is due to superoxide and hydrogen peroxide formation (Cruz et al 1978, Bulatovic et al 2002, Salas et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…These reactive by-products are important in the action mechanism of isoniazid. Bulatovic et al (2002) described the synergistic activity of plumbagin (a naturally occurring naphthoquinone) with isoniazid against M. tuberculosis and M. smegmatis. This synergic effect was easily prevented by the overexpression of superoxide-dismutase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hazbon suggested that resistance to INH and evolution of MDR strains is very complex and dynamic, involving various genes interaction and anti TB drug resistace phenotype ( Hazbon et al,2006;Bulatovic et al, 2002;Van Solingen et al, 2000). More extensive studies are needed to be able to explain mechanism of resistance to anti TB drugs.…”
Section: Susceptibility Of Katgser315thr Mutants To Anti Tb Drugsmentioning
confidence: 99%
“…Minimal inhibitory concentration of INH resistant isolates increase 20-200 times. With position of cytochrome oxidase super family peroxidase-catalase, it is suggested that Ser315 is close to active site of KatG so that Ser315Thr mutation infl uence enzyme activity of KatG (Heym et al, 1998;Bulatovic et al, 2002;Van Solingen et al, 2000.;Luo et al, 2013).…”
Section: Susceptibility Of Katgser315thr Mutants To Anti Tb Drugsmentioning
confidence: 99%